Salinity and Organic Feed Optimization for Artemia franciscana Culture: Differential Survival Responses to Chlorella vulgaris and Saccharomyces cerevisiae in Nauplii and Adults - Al Sulivany et al. (Iraqi Journal of Aquaculture, 2025)
Extensive research on the impact of salinity on artemia populations worldwide, there remains a gap in knowledge about the culture of artemia at different salinity levels with varying feed sources. So, this study aims to cultured Artemia franciscana in controlled conditions at different salinity concentration levels and feeds to check the survival rate and make available live feed sources to reduce cannibalism. This study benefits aquaculture, fulfilling the massive demand to produce brine shrimp at a low cost in the natural ecosystem to upgrade aquaculture production. Our results revealed a significant positive correlation between salinity and SR, with nauplii survival peaking at 90.23 ± 0.83% at 40 ppt. Adults similarly exhibited the highest SR (94.76 ± 65.77%) at 40 ppt. Dietary comparisons showed C. vulgaris outperformed Saccharomyces cerevisiae, with nauplii SR reaching 80.04 ± 4.55% versus 61.19 ± 4.55% (p < 0.005) and adult SR stabilizing at 90.9 ± 3.5% versus 57.6 ± 3.1% (p < 0.05) by day 41. Survival trends were inversely related to salinity for S. cerevisiae, suggesting nutrient limitations or metabolic stress. Conversely, Chlorella vulgaris supported incremental SR improvements, likely due to its rich fatty acid and protein profiles. These findings highlight the synergistic benefits of high salinity (35–40 ppt) and C. vulgaris diets in optimizing A. franciscana culture. In this study, A. franciscana showed a maximum survival rate of nauplii, and an adult was found at 40 ppt with two organic feeds, showing that C. vulgaris is considered a good potential feed with a maximum survival rate as compared to Baker´s yeast (S. cerevisiae).